Theory and practice of model transformations : 8th International Conference, ICMT 2015, held as part of STAF 2015, L'Aquila, Italy, July 20-21, 2015. Proceedings /: 8th International Conference, ICMT 2015, held as part of STAF 2015, L'Aquila, Italy, July 20-21, 2015. Proceedings. (2015) - Unknown
No abstract available